The role of sulfated steroid hormones in reproductive processes. Issue 172 (September 2017) - Geyer, Joachim; Bakhaus, Katharina; Bernhardt, Rita; Blaschka, Carina; Dezhkam, Yaser; Fietz, Daniela; Grosser, Gary; Hartmann, Katja; Hartmann, Michaela F.; Neunzig, Jens; Papadopoulos, Dimitrios; Sánchez-Guijo, Alberto; et al.
Abstract: Sulfated steroid hormones, such as dehydroepiandrosterone sulfate or estrone-3-sulfate, have long been regarded as inactive metabolites as they cannot activate classical steroid receptors. Some of them are present in the blood circulation at quite high concentrations, but generally sulfated steroids exhibit low membrane permeation due to their hydrophilic properties. However, sulfated steroid hormones can actively be imported into specific target cells via uptake carriers, such as the sodium-dependent organic anion transporter SOAT, and, after hydrolysis by the steroid sulfatase (so-called sulfatase pathway), contribute to the overall regulation of steroid responsive organs. To investigate the biological significance of sulfated steroid hormones for reproductive processes in humans and animals, the research group "Sulfated Steroids in Reproduction" was established by the German Research Foundation DFG (FOR1369). Projects of this group deal with transport of sulfated steroids, sulfation of free steroids, desulfation by the steroid sulfatase, effects of sulfated steroids on steroid biosynthesis and membrane receptors as well as MS-based profiling of sulfated steroids in biological samples. This review and concept paper presents key findings from all these projects and provides a broad overview over the current research on sulfated steroid hormones in the field of reproduction.